Analisis Dan Perancangan Sistem Informasi Distribusi Pada Pt Rudi Agung Agralaksana - Soyata, Agung Raga; Assegaff, Setiawan (Jurnal Manajemen Sistem Informasi, 2020)
In the data processing process of product distribution at PT. Rudi Agralaksana, still using conventional and not maximal methods in product data processing, data processing of product transportation, daily distribution data processing, monthly distribution data processing, which still occur errors and missing or damaged data reports. The purpose of this study is to analyze the needs of the distribution information system of PT. Rudi Agralaksana and designing web-based product distribution information prototype at PT. Rudi Agralaksana using UML (Unified Modeling Language). And as for the results of this study, distribution information system that is able to help staff in processing product data,transport products and distribution reports more easily and integrated with each other.information system is displayed in the form of production reports, product reports, reports transportation, distribution and information reports for agents as consumers of PT. Rudi Agung Agralaksana. So that it is expected to be implemented in managing distribution data at PT. Rudi Agung Agralaksana and it can fix the problem in the system before. The suggestion in this research is that the design of this system needs to be developed so that it can be applied to PT. Rudi Agung Agralaksana, and it can contribute to the development of science and technology in the information systems.